2003
DOI: 10.5194/angeo-21-627-2003
|View full text |Cite
|
Sign up to set email alerts
|

On ALADIN precipitation modeling and validation in an Alpine watershed

Abstract: Abstract. Highly resolved precipitation forecasts are necessary in many applications, especially in mountain meteorology and flash flood forecasts for small-to medium-sized alpine watersheds. Here we present precipitation forecasts simulated by the limited area model ALADIN applying different grid resolutions ( x = 10 km and 4 km). Target area of the investigations is the Alpine Ticino-Verzasca-Maggia watershed (total area: 2627 km 2 ).We discuss problems of validation of high-resolution precipitation forecast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Alternatively, it has been proposed to compare NWP and observed precipitation fields from the perspective of their spatial structure (Zepeda-Arce et al 2000;Harris et al 2001). This is in line with previous studies, attempting to use spatial spectral information to downscale NWP output to the high-resolution scales needed by impact models in hydrological (Schertzer et al 2007;Ahrens 2003;Ahrens et al 2003;Harris et al 2001;Tessier et al 1996) and now casting applications (Chumchean et al 2004;Bowler et al 2006). In fact, since the work of Wilson et al (1991), it has been clear that the study of the statistical variability of precipitation could be crucial, especially in view of its use in hydrological models.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Alternatively, it has been proposed to compare NWP and observed precipitation fields from the perspective of their spatial structure (Zepeda-Arce et al 2000;Harris et al 2001). This is in line with previous studies, attempting to use spatial spectral information to downscale NWP output to the high-resolution scales needed by impact models in hydrological (Schertzer et al 2007;Ahrens 2003;Ahrens et al 2003;Harris et al 2001;Tessier et al 1996) and now casting applications (Chumchean et al 2004;Bowler et al 2006). In fact, since the work of Wilson et al (1991), it has been clear that the study of the statistical variability of precipitation could be crucial, especially in view of its use in hydrological models.…”
Section: Introductionmentioning
confidence: 85%
“…In particular, it was suggested that building downscaling methodologies in combination with numerical models is important, so as to reproduce the variability of precipitation at the spatial and temporal scales resolved by impact models. For this purpose, a promising approach has used the scaling properties of the precipitation field, relating the small-and large-scale statistical structures (Ahrens 2003;Ahrens et al 2003;Waymire 1985;Lovejoy and Schertzer 1985). Using radar precipitation estimates at high space-time resolution, several studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these uncertainties have minor impact on the conclusions drawn here about the importance of scaling and the performance of stochastic downscaling. WaSiM‐ETH simulations in the TVM watershed have already been used successfully as a validation tool of precipitation data generated by meteorological models [ Jasper et al , 2002; Ahrens et al , 2003]. Simulated runoff has been sensitive to amount and variability of precipitation input in these validation experiments.…”
Section: Evaluation By Hydrological Modelingmentioning
confidence: 99%
“…Therefore stochastic downscaling of rain is preferred in this study. The alternative, downscaling by nested deterministic meteorological simulations is applied, for example, in the work of Ahrens et al [2003].…”
Section: Introductionmentioning
confidence: 99%
“…This has been done in several studies (e.g. Bica et al, 2011;Valéry et al, 2009Valéry et al, , 2010Ahrens et al, 2003;Jasper and Kaufmann, 2003;Kunstmann and Stadler, 2005;Jasper et al, 2002). The common basis of these studies was to indirectly gain information on catchment rainfall by comparing simulated runoff results with observations.…”
Section: Catchment Precipitation From Runoff Observations Through Invmentioning
confidence: 99%